THE ROLE OF GRAMMAR IN ENGLISH FLUENCY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Grammar plays a pivotal role in achieving fluency in English, serving as the structural foundation upon which effective communication is built. This article explores the importance of understanding and applying grammatical rules to enhance language proficiency. While some language learners may view grammar as a tedious and challenging aspect of language acquisition, mastering it is essential for accurate and articulate expression. We will discuss the balance between grammatical correctness and natural language use, emphasizing that fluency encompasses both precision and fluidity. Practical strategies and exercises for integrating grammar into everyday use will be provided, alongside insights into common grammatical pitfalls and how to avoid them. By recognizing the critical role of grammar, learners can develop greater confidence and competence in their English communication skills.